2008
DOI: 10.1111/j.1751-7915.2008.00063.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of and resistance to quinolones

Abstract: SummaryFluoroquinolones are an important class of wide‐spectrum antibacterial agents. The first quinolone described was nalidixic acid, which showed a narrow spectrum of activity. The evolution of quinolones to more potent molecules was based on changes at positions 1, 6, 7 and 8 of the chemical structure of nalidixic acid. Quinolones inhibit DNA gyrase and topoisomerase IV activities, two enzymes essential for bacteria viability. The acquisition of quinolone resistance is frequently related to (i) chromosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
313
2
13

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 383 publications
(341 citation statements)
references
References 202 publications
(306 reference statements)
13
313
2
13
Order By: Relevance
“…However, multiple studies showed that gyrB and parE were not common target sites for mutation in Gram-negative pathogens (2,11,30,40) and that gyrA mutation was the most common first mutational step in quinolone resistance. The in vitro model utilized in our studies also could not mimic in vivo conditions, such as the pathology of infection, host-defense mechanisms, virulence, and metabolic behavior of the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple studies showed that gyrB and parE were not common target sites for mutation in Gram-negative pathogens (2,11,30,40) and that gyrA mutation was the most common first mutational step in quinolone resistance. The in vitro model utilized in our studies also could not mimic in vivo conditions, such as the pathology of infection, host-defense mechanisms, virulence, and metabolic behavior of the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…They result from both chromosomally encoded mutations and plasmid-mediated quinolone resistance (10). The first mechanism includes mutations of the target genes gyrA and gyrB, which encode DNA gyrase, and parC and parE, encoding topoisomerase IV (29,35,41,43,44), as well as mutations responsible for a decrease in quinolone permeability, either by increasing the efflux or by decreasing the expression of outer membrane proteins used as entrance channels (5,7,9,34).…”
mentioning
confidence: 99%
“…Gyrase is primarily responsible for introducing negative supercoils into conformationally constrained DNA, while topoisomerase IV primarily resolves linked chromosome dimers at the conclusion of DNA replication [14][15][16][17] . Inhibitors of DNA gyrase typically also inhibit bacterial topoisomerase IV, although the relative importance for expression of antibacterial activity can vary depending on the inhibitor and the bacterial species [18][19][20] . Recently 21 , we showed for the first time inhibitory potency of two 4-benzoylthiosemicarbazides towards bacterial topoisomerase IV ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%